Effect of bone-marrow-derived mesenchymal stem cells on the rate of orthodontic tooth movements in rabbits: BM-MSCs and orthodontic tooth movement - Jasim Othman, Rawand; Fawzi Chawshli, Omar (Cellular and Molecular Biology, 2024)
Mesenchymal stem cells from bone marrow, such as bone marrow aspirate concentrate (BMAC) and cultured and isolated bone marrow mesenchymal stem cells (BM-MSCs), have been used as therapeutic alternatives to enhance remodeling in the bone. Objective: This study aimed to evaluate the effects of BMAC and BM-MSCs on orthodontic tooth movements in rabbits. Methods: A100- gram nickel–titanium closed-coil springs were used to initiate orthodontic tooth movement of the lower first premolars in 35 male New Zealand rabbits for 21 days. Using a split-mouth design, autologous BMAC or BM-MSCs were submucosally injected into the right sides of the lower jaw, while the left sides served as the control. On days 7, 14, and 21, a three-dimensional digital model scan was used to measure the amount of tooth movement. The microfocus computed tomography (Micro-CT) and histological findings were examined on day 0 as the baseline measurement and on days 7, 14, and 21. Results: Compared to the control group, the quadrant receiving BMAC and BM-MSCs had a considerably greater amount of tooth movement. Histomorphometric analysis revealed that both BMAC and BM-MSCs had significantly higher numbers of osteoclasts and active bone-resorptive lacunae. The resorptive changes were greater in the BMAC and BM-MSCs groups than in the control group. Conclusion: The submucosal injection of BMAC and BM-MSCs accelerates orthodontic tooth movement (OTM) by decreasing bone density and supplying more osteoclast progenitor cells.